Magneto-Seebeck effect in an ITO/PEDOT:PSS/Au thin-film device - Hongfeng Wang; Qing Liu; Jeremy Tisdale; Ling Xu; Yuchun Liu; Bin Hu (AIP Advances, 2016)
This article reports giant magnetic field effects on the Seebeck coefficient by exerting a Lorentz force on charge diffusion based on vertical multi-layer ITO/PEDOT:PSS/Au thin-film devices. The Lorentz force, induced by an external magnetic field, changes the charge transport and consequently generates angular dependent magnetoresistance. The proposed mechanism of the magneto-Seebeck effect is proved by measuring the magnetoresistance at a parallel, 45o and perpendicular angle to the temperature gradient. The gradual change of the magnetoresistance from a parallel to perpendicular angle indicates that the Lorentz force is a key driving force to develop the magneto-Seebeck effect. Therefore, our experimental results demonstrate a magnetic approach to control the thermoelectric properties in organic materials.